Luminescent organic-inorganic hybrid electrolytes for smart building glazing - Cardoso, Marita Alves (2021)
There is a global need to improve the building energy generation efficiency in the new generation of buildings, so called zero-energy buildings (ZEBs). One strategy includes the development of smart windows based on electrochromic devices (ECDs) coupled to luminescent layers and luminescent solar concentrators (LSCs). New materials based on lanthanide complexes with high quantum efficiency incorporated in appropriate host matrices prepared by solgel chemistry opens challenging opportunities for the development of new devices with remarkable electro-optical performance and foreseen application as smart windows for ZEBs. In this thesis, new electrolytes based on organicinorganic hybrids doped with an ionic liquid allowed the production of ECDs with high visible and NIR transparency and voltage-actuated dual coloration tuning, enabling three-mode operation (bright hot, semi-bright warm, and dark cold). The ECD delivers a number of extraordinary features, in particular high switching efficiency and optical modulation, good cycling stability, large coloration efficiency, excellent optical memory, and unusual self-healing ability following mechanical stress. In addition, new lanthanide ions (Ln3+ = Nd3+, Eu3+, Tb3+, Yb3+)-doped surface functionalized ionosilicas (ISs) were produced, characterized and embedded in poly(methyl methacrylate) yielding transparent films with negligible self-absorption with potential to be used LDS layers, and LSC into a single device. The significant absolute increase observed in the PV cell external quantum efficiency (EQE~32% between 300-360 nm relatively to the bare PV cell) supports the applicability of the developed materials for ZEBs.